SOCIAL CAPITAL IN MANAGING COMMUNITY PLANTATION FOREST: A CASE STUDY AT KPH BOALEMO, GORONTALO PROVINCE - Sylviani, Sylviani; Suka, Aneka Prawesti; Surati, Surati; Kurniasari, Dewi Ratna (Indonesian Journal of Forestry Research, 2020)
Community Plantation Forest (HTR) is one among alternatives expected to fulfill the needs of timber. Limited capital, which is simply known as financial capital, is considered as the main problem in HTR development. However, there is also other capital but less known and understood namely social capital. This study aims to determine the social capital that can be utilized in HTR management. The study was conducted in Rumbia Village, Boalemo District, Gorontalo Province. The data collected was analyzed using descriptive qualitative method in three steps: data reduction, data display and verification. In this study, the social capital is discussed in its dimensions of trust, norm and network. Results of the study show that strengthening social capital in its dimension of trust, norm, and network would encourage independence of both the farmers and forest farmer groups in HTR management. If the social capital does not work properly, gap among farmers could occur and even becomes a barrier or limits in involvement of members of the farmer group in the management of HTR. The farmers had high trust to forestry extension officer. It became a dimension of social capital that should be developed further in HTR management to reach optimally benefits from HTR land. In addition, the farmers also had a high compliance to social norms of traditions, religion and customary rules. The social capital hold by the farmers should be addressed in proper way by local and central government in order to develop successful HTR management.